High-Intensity Skill Training to Improve Fast-Break Performance among Young Basketball Players - Muhammad Hussein Wali; Haider Naeem Shamam (Wahid Hasyim University, 2026)
Objectives: This study aimed to examine the effect of high-intensity skill training on fast-break performance among young basketball players. Materials and Methods: A one-group experimental design with pre-test and post-test measurements was used. The participants were 10 male youth basketball players aged 16–17 years from Al-Kut Sports Club. The training program lasted eight weeks and consisted of 24 sessions, conducted three times per week. Each session included 30 minutes of skill-based high-intensity exercises focusing on dribbling, long passing, layup scoring, rebounding, and fast-break execution. Data were analyzed using SPSS with paired-sample t-tests. Results: The findings showed significant improvements in dominant-arm dribbling, layup scoring between obstacles, layup accuracy, rebounding/follow-up performance, and total fast-break execution time. However, long passing did not show a statistically significant improvement. Conclusions: High-intensity skill training was effective in improving several fast-break-related skills among young basketball players, particularly dribbling speed, layup performance, rebounding actions, and overall fast-break execution. Coaches are encouraged to integrate game-like high-intensity skill drills into youth basketball training programs.